2019
DOI: 10.1186/s12889-019-7196-0
|View full text |Cite
|
Sign up to set email alerts
|

Office workers’ experiences of attempts to reduce sitting-time: an exploratory, mixed-methods uncontrolled intervention pilot study

Abstract: Background Office workers typically sit for most of the workday, which has been linked to physical and mental ill-health and premature death. This mixed-methods study sought to identify barriers and facilitators to reducing sitting and increasing standing among office workers who received an intervention prototype (the ‘ReSiT [Reducing Sitting Time] Study’). The intervention comprised a sit-stand workstation and tailored advice to enhance motivation, capability and opportunity to displace sitting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 35 publications
2
37
0
2
Order By: Relevance
“…People often express surprise upon realizing their sitting time [39], suggesting they do not consciously attend to it. Raising awareness, by for example objectively monitoring and providing retrospective feedback on time spent sitting, can motivate people to reduce their sitting time [4042]. Interventions might also reduce sitting indirectly, by targeting actions that incur sitting.…”
Section: Discussionmentioning
confidence: 99%
“…People often express surprise upon realizing their sitting time [39], suggesting they do not consciously attend to it. Raising awareness, by for example objectively monitoring and providing retrospective feedback on time spent sitting, can motivate people to reduce their sitting time [4042]. Interventions might also reduce sitting indirectly, by targeting actions that incur sitting.…”
Section: Discussionmentioning
confidence: 99%
“…Users indicated that they preferred to use the standing workstation when completing work tasks which did not require high levels of concentration, such as sending emails. Specific work tasks associated with standing have also been indicated in other studies [ 22 , 25 , 40 ]. Moreover, a recent study found that people did not identify “sitting” as an activity in and of itself, but rather thought of sitting in relation to the task they performed (e.g.…”
Section: Discussionmentioning
confidence: 84%
“…Users suggested that an introductory phase could be helpful for non-users to increase the use of the standing option. Still, long periods of absence from work could trigger relapse as indicated elsewhere [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such low levels of physical activity can have negative effects on health, wellbeing and quality of life [24]. Over the past five decades, jobs and occupations have increased the amount of seated technical work or desk-based office work [25]. A systematic review reveals that people with more active jobs had lower all-cause or cardiovascular disease mortality risk than those with jobs that involved mostly sitting [26].…”
Section: Home-based Teleworking Sedentary Lifestyle and Ideal Posturesmentioning
confidence: 99%